Dead or alive - Clancy, Tom, 1947-2013 (Clancy, Tom, 1947-2013. Jack Ryan novel., 2010)
Jack Ryan, Jr. and his Campus colleagues John Clark and Ding Chavez, go after a vicious terrorist mastermind--the Emir--and they will bring him in ... dead or alive.